The use of dexmedetomidine in endoscopic surgical procedures ofthe nasal cavity in children. - R. I. Nasirova; A. J. Jumshudov; E. M. Nasibova (Pediatric Anesthesia and Critical Care Journal, 2024)
Introduction In recent years, dexmedetomidine has come to the fore- front in pediatric anesthesiology. In recent years, this drug has begun to be widely used in surgical interven- tions of the nasal cavity in children. Surgical interven- tions in the nasal cavity are classified as low-traumatic and low-volume operations, but they are accompanied by fairly intense pain. Dexmedetomidine is widely used in cardiac surgery, neurosurgery, gynecology and dentistry. However, there is not enough experience in using it in otorhinolaryngology. Purpose of the study: Optimization of anesthesia during endoscopic surgical interventions in the nasal cavity in children. Material and Methods In the period from 2022 to 2024, 106 planned endoscopic surgical operations of the nasal cavity were performed in patients aged 10-15 years under local anesthesia and with so-called conscious sedation at the AMU surgical clinic. Patients were randomized into 2 groups: main (n=53) and control (n=53). Patients in the main and control groups underwent septoplasty surgery. Patients in the main group received dexmedetomidine as sedation, and mid- azolam was used as sedation in the control group. Results In the main group, the average consumption of fentanyl was 50 ± 20 mcg, while in the control group its consump- tion was 100 ± 25 mcg. The consumption of local anes- thetic in the main group ranged from 3.0 to 6.0 ml de- pending on the operation, while in the control group it ranged from 4.0 to 8.0 ml. During intraoperative pain as- sessment on the BPS-NI pain scale, patients in the main group scored 3-4 points, and in the control group 4-10 points, respectively Conclusion Intraoperative sedation with dexmedetomidine in combi- nation with local anesthesia can be recommended as an alternative to general anesthesia for endoscopic nasal sur- gery.